Host identity shapes Endozoicomonas composition in coral microbiomes across depths and marine protected areas at Little Cayman Island - Madelaine L. Brown; Andrew J. Maritan; Gretchen Goodbody-Gringley; Matthew L. Doherty; Alex D. Chequer; Frank J. Stewart; Zoe A. Pratte (Coral Reefs, 2026)
The bacterial genus Endozoicomonas is prevalent and abundant in the microbiome of many corals, but the combination of environmental and host factors shaping its distribution remains uncertain. In this study, we used 16S rRNA gene sequencing to examine the distribution of Endozoicomonas across hard ( Porites astreoides , Montastraea cavernosa , Agaricia spp.) and soft coral ( Muricea spp., Gorgoniidae, Cladiellidae, Malacalcyonacea) microbiomes across a depth gradient from shallow (4.5 m) to upper mesophotic zones (36.6 m) at four sites around the Little Cayman Island, including two marine protected areas. Endozoicomonas was abundant across all coral microbiomes, with soft corals exhibiting near-total dominance (relative abundance range 0.1–99%, median 55.3%) by this genus and notable abundances (range 0–96%, median 22.2%) in hard corals. Endozoicomonas composition was strongly structured by coral host identity across sites and depths, with each coral type harboring two to four unique Endozoicomonas amplicon sequence variants. Site and depth also contributed to Endozoicomonas abundance in soft and hard corals, respectively, where relative abundances were highest at unprotected sites in soft corals and in shallow to mid photic zones in hard corals. These findings suggest that Endozoicomonas abundance is shaped by both coral host identity and local environmental conditions.

Fate tracking of Acropora cervicornis colonies post-outplanting reveals genotype-specific responses to marine heatwaves - Gretchen Goodbody-Gringley; Brett D. Jameson; Haley A. Davis; Janna L. Randle; Matthew L. Doherty; Jack V. Johnson; Alex D. Chequer; John F. Bruno (Coral Reefs, 2026)

Depth partitioning of mesophotic reef fish communities on Pickle Bank seamount - Jack V. Johnson; Alex D. Chequer; Gretchen Goodbody-Gringley (Frontiers in Marine Science, 2025)
Mesophotic coral ecosystems (MCEs)—reefs below 30m depth—represent distinct ecological communities that are under threat from local (e.g., fishing) and global (e.g., climate change) disturbances. However, most MCEs remain unexplored, and their ecological communities are not well characterized. MCEs on remote offshore seamounts are further unexplored and provide the opportunity to assess assembly rules from comparatively less disturbed MCEs, given their remoteness from settlements with high human population densities. Here, we characterize the fish community from the remote offshore seamount of Pickle Bank in the Central Caribbean Sea, exploring differences in the fish community at a 25m depth compared to the mesophotic zone at a 45m depth. We found differences in species composition between the depths, with a significantly higher abundance of fish at mesophotic depths, while species diversity and species richness were significantly higher at the shallow sites. Species from Labridae and Scaridae dominated the biomass at the shallow sites, while species in the family Carangidae dominated biomass in the mesophotic zone. There were also differences in the community composition of trophic guilds between depths, with higher macrocarnivore biomass, macrocarnivore abundance, and omnivore abundance at deep sites compared to shallow sites. Despite the logistical challenges and limitations associated with accessing MCEs on offshore seamounts, these data provide compelling evidence to the growing body of literature documenting MCEs as unique habitats warranting further data collection to obtain a holistic understanding of shallow and mesophotic seamount ecosystems.

Phenotypic variability of Montastraea cavernosa and Porites astreoides along a depth gradient from shallow to mesophotic reefs in the Cayman Islands - Matthew L. Doherty; Alex D. Chequer; Tali Mass; Gretchen Goodbody-Gringley (Coral Reefs, 2024)
Phenotypic variability is the ability of the same species to express different phenotypes under different environmental conditions. Several coral species that exist along a broad depth distribution have been shown to differ in skeletal morphology and nutrient acquisition at different depths, which has been attributed to variability in response to differing levels of light availability. This study examined the phenotypic variability of two common depth generalist corals, Montastraea cavernosa and Porites astreoides, along a gradient from 10 to 50 m in the Cayman Islands, by examining changes in skeletal morphology, photophysiology, symbiont cell density, and chlorophyll concentration. Skeletal features of M. cavernosa were found to increase in size from 10 to 30 m, but returned to smaller sizes from 30 to 50 m, while P. astreoides skeletal features continued to increase in size from 10 to 40 m. No differences were observed in either symbiont density or chlorophyll concentration across depths for either species. However, all photophysiological parameters exhibited significant depth-dependent variations in both species, revealing adaptive strategies to different light environments. These results suggest that both species have high variability in response to depth. Patterns of skeletal morphology and photophysiology, however, suggest that M. cavernosa may be more variable in regulating photosynthetic efficiency compared to P. astreoides , which likely facilitates the broader depth distribution of this species.

Ecological Drivers of Invasive Lionfish (Pterois volitans and Pterois miles) Distribution Across Mesophotic Reefs in Bermuda - Gretchen Goodbody-Gringley; Corey Eddy; Joanna Maria Pitt; Alex D. Chequer; Struan Robertson Smith (Frontiers in Marine Science, 2019)

Large-scale invasion of western Atlantic mesophotic reefs by lionfish potentially undermines culling-based management - Dominic A. Andradi-Brown; Mark J. A. Vermeij; Marc Slattery; Michael Lesser; Ivonne Bejarano; Richard Appeldoorn; Gretchen Goodbody-Gringley; Alex D. Chequer; Joanna M. Pitt; Corey Eddy; Struan R. Smith; Eran Brokovich; et al. (Biological Invasions, 2017)